2015
DOI: 10.1007/s11336-015-9465-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically Correct Standardization of Person-Fit Statistics Beyond Dichotomous Items

Abstract: The [Formula: see text] statistic (Drasgow et al. in Br J Math Stat Psychol 38:67-86, 1985) is one of the most popular person-fit statistics (Armstrong et al. in Pract Assess Res Eval 12(16):1-10, 2007). Snijders (Psychometrika 66:331-342, 2001) derived the asymptotic null distribution of [Formula: see text] when the examinee ability parameter is estimated. He also suggested the [Formula: see text] statistic, which is the asymptotically correct standardized version of [Formula: see text]. However, Snijders (Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(83 citation statements)
references
References 36 publications
7
76
0
Order By: Relevance
“…The adjustment of Snijders () was also applied to the infit ( W ) and outfit ( U ) statistics (e.g., Wright & Masters, ) by Magis, Beland and Raiche () and to the standardized extended caution indices (Tatsuoka, ) by Sinharay (). Sinharay () extended the adjustment of Snijders (), which applies only to dichotomous items, to tests involving both dichotomous and polytomous items.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjustment of Snijders () was also applied to the infit ( W ) and outfit ( U ) statistics (e.g., Wright & Masters, ) by Magis, Beland and Raiche () and to the standardized extended caution indices (Tatsuoka, ) by Sinharay (). Sinharay () extended the adjustment of Snijders (), which applies only to dichotomous items, to tests involving both dichotomous and polytomous items.…”
Section: Introductionmentioning
confidence: 99%
“…Magis et al. (, ), Sinharay (, ), Snijders (), and van Krimpen‐Stoop and Meijer () used the maximum likelihood estimate (MLE), the weighted likelihood estimate (WLE; Warm, ), and the modal a posteriori (MAP) estimate of the examinee ability with the adjustment of Snijders (). Magis et al.…”
Section: Introductionmentioning
confidence: 99%
“…This method is flexible in that different weighting mechanisms can be used in the same general framework. In this study the weights are derived from the normalized p-value of Sinharay's (2016a) person fit statistic ! " * , but it does not necessarily have to be so.…”
mentioning
confidence: 99%
“…A comparison of PFSs for polytomous items using real data may be of interest. Parametric PFSs for polytomous items were suggested by researchers such as Drasgow et al (1985) and Sinharay (2016c) and nonparametric PFSs were suggested by researchers such as Emons (2008). Sixth, WLEs (Warm, 1989) were used as the ability estimates in this article.…”
Section: Resultsmentioning
confidence: 99%